Neural Correlates of Hypokinetic Dysarthria and Mechanisms of Effective Voice Treatment in Parkinson Disease. (December 2018) - Baumann, Alexander; Nebel, Adelheid; Granert, Oliver; Giehl, Kathrin; Wolff, Stephan; Schmidt, Wiebke; Baasch, Christin; Schmidt, Gerhard; Witt, Karsten; Deuschl, Günther; Hartwigsen, Gesa; Zeuner, Kirsten E.; et al.
Background. Hypokinetic dysarthria is highly prevalent in idiopathic Parkinson disease (PD), and effectiveness of high-intensity voice treatment is well established. However, the neural correlates remain largely unknown. Objective. We aimed to specify cerebral pathophysiology of hypokinetic dysarthria and treatment-induced changes using functional magnetic resonance imaging (fMRI). Methods. We used fMRI to investigate healthy controls (HCs) and patients with idiopathic PD–associated dysarthria before and after treatment according to the Lee Silverman Voice Treatment LOUD (LSVT). During fMRI, participants covertly read sentences with normal (eg, conversation in a quiet room) or high (eg, shouting on a windy beach) intensity. In addition, we tested LSVT effects on intelligibility and different speech features (intensity, pitch, articulation). Results. LSVT effectively improved intelligibility, articulation, and pitch in patients. Covert high-intensity speech compared with covert normal-intensity speech led to increased activation of mainly secondary motor areas and bilateral superior and medial temporal regions. Prior to LSVT, patients showed less activity in several speech-associated areas compared with HCs. As a neural correlate of effective LSVT, increased right-sided superior temporal activity correlated with improved intelligibility. Conclusion. This is the first brain imaging study using a covert speech paradigm in PD, which revealed cortical hypoactivation as correlate of hypokinetic dysarthria. Furthermore, cortical correlates of effective LSVT treatment colocalized with the neuronal network, showing increased activation during high- versus normal-intensity speech generation.